Overview Of Knowledge About Bullying Among Level I Students At Santa Elisabeth Medan College Of Health Sciences 2024 - Helinida Saragih; Indra Hizkia P; Ester Lamtiurma Situmorang (Jurnal Kesehatan Amanah, 2024)
Bullying can occur for various reasons, such as injustice, ignorance, or the desire to dominate or control other people. Factors such as differences in physical strength, culture, or even the perpetrator's lack of self-confidence also influence the occurrence of bullying. It involves an urge to harm, which can drive a person to perform physical, psychological, or verbal acts that cause suffering to the victim. The impact is very significant for perpetrators who tend to be aggressive and have bullying tendencies, as well as for victims who often experience anxiety, even depression, which can sometimes lead to thoughts of committing suicide. The aim of this research is to identify a picture of knowledge about bullying among level I students. This research method is descriptive. The sample in this research are 127 respondents with sampling technique using the Simple Random Sampling technique. This research instrument uses a questionnaire. The results of the research show a picture of knowledge about bullying among level I students in good knowledge category of 80.3%, sufficient knowledge of 11.8%, and poor knowledge of 7.9%. It is hoped that educational institutions can provide seminars on bullying and anti-bullying policies within the Santa Elisabeth Medan College of Health Sciences.